A study on factors that influence customer perception at Charisma Technology Cyber Cafe, Kuala Kangsar, Perak / Azlan Al-Hafiz Mazlan - Mazlan, Azlan Al-Hafiz (Faculty of Business and Management, 2005)
This research is aimed to determine factors that influence customer perception towards CTCC service and which the most influencing factor from four independent variables is under studied. The research involves two variables; dependent variable (customer perception) and independent variables (pricing, service quality, advertising and sales promotion). There are 140 respondents among customers at CTCC Kuala Kangsar involved in this research. Information will be gathered using stratified data sampling method. Tool that will be used to analyze data is by using the Statistical Package of Social Science (SPSS). At the end of this project paper, the researcher can concluded that there is a positive relationship between dependent variable with pricing and service quality, while other two independent variables, advertising and sales promotion have no positive relationship.